2011
DOI: 10.1002/dev.20535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of siblings on early development: A potential contributor to personality differences in mammals

Abstract: Although most mammals grow up in the company of same or different age sibs (or half sibs), surprisingly little attention has been given to how relations among them might influence the development of individual differences in morphology, physiology, and behavior. Here we review evidence from our work on domestic and wild European rabbits, and more recently on laboratory rats, mice, and domestic cats, supporting the proposition that in mammals early sibling relations contribute to the development of individual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 70 publications
4
79
0
Order By: Relevance
“…But also other physiological parameters, such as the development of HPA axis functionality are reported to be slower in young from larger litters (Rödel, Meyer, Prager, Stefanski, & Hudson, 2010). Such significant differences in the physical and physiological development are not only apparent among litters but also within litters between pups born with higher and lower starting mass (Bautista, Garcia-Torres, Martínez-Gómez, & Hudson, 2008;Hudson et al, 2011;Rödel, Bautista, García-Torres, Martínez-Gómez, & Hudson, 2008).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…But also other physiological parameters, such as the development of HPA axis functionality are reported to be slower in young from larger litters (Rödel, Meyer, Prager, Stefanski, & Hudson, 2010). Such significant differences in the physical and physiological development are not only apparent among litters but also within litters between pups born with higher and lower starting mass (Bautista, Garcia-Torres, Martínez-Gómez, & Hudson, 2008;Hudson et al, 2011;Rödel, Bautista, García-Torres, Martínez-Gómez, & Hudson, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…These studies show that individuals can be assigned to distinct groups or at least can be ordered along a continuum with respect to parameters such as, for example, their levels of boldness, aggressiveness, or tendency to explore novel environments. This gives rise to several questions on the proximate causes (Hudson et al, 2011), physiological correlates (Kralj-Fišer, Weiß, & Kotrschal, 2010), adaptive value (Boon, Réale, & Boutin, 2007;Eccard & Rödel, 2011;Réale, Martin, Coltman, Poissant, & Festa-Bianchet, 2009), and evolution of this phenomenon (Wolf, Van Doorn, Leimar, & Weissing, 2007), which is often referred to as animal personality, behavioral Developmental Psychobiology Heiko G. Rö del 1 syndrome, temperament, or coping style Mason, 1984).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sulloway (2010) has suggested that one major force leading to such differential development of personality is character displacement as observed in different closely related species such as the Darwin's finches. In this sense then niche construction is a very active process that is most likely to occur in closed social systems like children within one family, chicks in a nest or young within one litter (Hudson, Bautista, Reyes-Meza, Morales-Montor, & Rödel, 2011). In such a situation where competition for the same resources becomes extreme any small differentiation in use of the environment will diminish competitive and potentially agonistic interactions and reward social differentiation.…”
Section: Niche Picking and Niche Constructionmentioning
confidence: 99%
“…Increasing evidence suggests that aggression and coping style of an individual animal can depend on the conditions experienced during early life, including the size of the litter it is born into (reviewed in Hudson, Bautista, Reyes, Morales Montor, & Rödel, 2011). Individuals of small litters of rats and rabbits were more aggressive and bolder compared to individuals of the same species and same sex that were born into larger ones (Rödel & Meyer, 2011;.…”
Section: Discussionmentioning
confidence: 99%